The Effect of the Guessing the Sound (GATSU) Game on Android Mobile Phones on the Decrease in Auditory Hallucinations in Schizophrenia - Rizky Gumilang Pahlawan; Istianah Istianah; Ahamd Arifin; Syifa FA; Icih Susanti (Indonesian Journal of Global Health Research, 2026)
Handling of auditory hallucination symptoms in schizophrenia patients is very important because schizophrenia is a chronic severe mental disorder that lasts throughout life and has safety risks. Efforts to treat hallucinations other than pharmacological therapy need to be combined with non-pharmacological therapy. The non-pharmacological therapy method that has been present at this time still uses a direct method and requires several components for its implementation so that it needs an update effort with an accessible and efficient method, one of which is the Android-based voice guessing game (GATSU). The purpose of this study was to determine the effect of the Android-based voice guessing game (GATSU) on reducing auditory hallucinations in schizophrenia patients. This study used a quantitative approach with a quasi-experimental design with a Nonequivalent Control Group. The experimental group was given treatment with an Android-based mobile phone GATSU 5 times with a duration of 5-10 minutes each time and the control group was given treatment to guess images and sounds directly with 5 times with a duration of 10 minutes. Sample in this study was 30 respondents and sampling technique in this study used accidental sampling sampling divided into 2 groups15 experimental groups and 15 control groups.  The measuring instrument used auditory hallucination rating scale (AHRS) The instrument has through validity and reliability testing and has been declared valid and reliable for measuring auditory hallucinations. The results of the study obtained hallucination scores in the experimental group with a median pretest score of 42 and a median posttest score of 7. in the control group the median pretest score was 30 and a median posttest score of 27. Based on the results of the Wilcoxson test in the experimental group, a P-Value of 0.001 was obtained, the control group obtained a P-Value of 0.255. And in the experimental group and the control group, a Value of 0.001 was obtained . It can be concluded that Gatsu Therapy has a significant effect in reducing hallucination scores compared to the control group.